Mpox: Fifty-Nine Consecutive Cases from a Mexican Public Hospital; Just the Tip of the STIs Iceberg - Esteban González-Díaz; Christian E. Rodríguez-Lugo; Sergio Quintero-Luce; Sergio Esparza-Ahumada; Héctor Raúl Pérez-Gómez; Rayo Morfín-Otero; Marina de Jesus Kasten-Monges; Sara A. Aguirre-Díaz; Marisela Vázquez-León; Eduardo Rodríguez-Noriega (MDPI AG, 2023)
Monkeypox (Mpox) is a zoonotic viral infection endemic to Africa, which has caused a global outbreak since April 2022. The global Mpox outbreak is related to Clade IIb. The disease has primarily affected men who have sex with men. Skin lesions are concentrated in the genital area, with lymphadenopathy as well as concurrent sexually transmitted infections (STIs). This is an observational study of adult patients with a recent development of skin lesions and systemic symptoms, which could not be explained by other diseases present. Fifty-nine PCR-positive patients with prominent skin lesions in the genital area (77.9%), inguinal lymphadenopathy (49.1%), and fever (83.0%) were included. Twenty-five (42.3%) were known to be living with human immunodeficiency virus (HIV), and 14 of the HIV-naïve subjects (51.9%) were found to be positive during workup, totaling 39 (66.1%) patients with HIV. Eighteen patients (30.5%) had concurrent syphilis infections. It is worrisome that Mpox is present in large metropolitan areas of Mexico, but the underlying growth of cases of HIV infection and other STIs has not been well studied and should be evaluated in all at-risk adults and their contacts.